2008
DOI: 10.1002/jmri.21322
|View full text |Cite
|
Sign up to set email alerts
|

Transit delay and flow quantification in muscle with continuous arterial spin labeling perfusion‐MRI

Abstract: Purpose: To test the hypothesis that flow measurements using continuous arterial spin labeling (CASL) magnetic resonance imaging (MRI) in muscle depend upon transit delay, and examine the repeatability of CASL measurements. Materials and Methods:A total of 23 healthy subjects underwent CASL imaging of the calf, foot, and forearm with varying postlabeling delay (PLD ϭ 1000, 1500, and 1900 msec). Experiments were conducted on a 3.0T system. An orthopedic tourniquet system was employed to create a five-minute per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 40 publications
(52 reference statements)
1
23
0
Order By: Relevance
“…If the PLD is too short, the label remaining in large vessels leads to regional flow overestimation, whereas the signal-to-noise ratio can be compromised if the PLD is too long. Our previous study suggested that arterial transit times in the skeletal muscle may be prolonged and that venous outflow of unextracted label during hyperemia occurs (48). These confounds can be minimized by using a relatively long PLD (1,900 ms) to maximize inflow along with a relatively long TR (4 s) to allow unextracted label to fully decay.…”
Section: Discussionmentioning
confidence: 98%
“…If the PLD is too short, the label remaining in large vessels leads to regional flow overestimation, whereas the signal-to-noise ratio can be compromised if the PLD is too long. Our previous study suggested that arterial transit times in the skeletal muscle may be prolonged and that venous outflow of unextracted label during hyperemia occurs (48). These confounds can be minimized by using a relatively long PLD (1,900 ms) to maximize inflow along with a relatively long TR (4 s) to allow unextracted label to fully decay.…”
Section: Discussionmentioning
confidence: 98%
“…To account for the temporal offset between the control and label image series, adjacent control data were averaged to yield a temporally matched control series. 33 Perfusion was computed from the ROI-averaged signal intensity in pairs of label and temporally matched control data according to the appropriate models (Eqs. 2 and 3) for each ASL method as described in the introduction with PLD = 1900 msec in pCASL, 940 msec in PASL, T 1,blood ≈ T 1,tissue = 1420 msec.…”
Section: Methodsmentioning
confidence: 99%
“…The perfusion offset was corrected by subtracting the average perfusion during the period of cuff occlusion from each time point, as perfusion is assumed to be zero during the period of proximal arterial occlusion. 32 For each muscle, the peak perfusion and time to peak perfusion (TTP Perf ) were recorded from the dynamic time course data (Figure 1c). …”
Section: Methodsmentioning
confidence: 99%